Platelet count and risk of major bleeding in venous thromboembolism - Johnsen, Håkon Sandbukt; Brækkan, Sigrid Kufaas; Morelli, Vania Maris; Hansen, John-Bjarne (Platelets, 2020)
The relationship between platelet count and risk of major bleeding in patients with venous thromboembolism (VTE) during anticoagulation remains unclear. We therefore investigated the association between platelet count, measured at VTE diagnosis and before the thrombotic event, and risk of major bleeding. Participants comprised 744 patients with incident VTE derived from the Tromsø Study. Major bleedings were recorded during the first year after VTE. Cox-regression was used to calculate hazard ratios (HRs) for major bleeding across platelet count quartiles. There were 55 major bleedings (incidence rate 9.1/100 person-years, 95% confidence interval [CI] 7.0–11.8). The major bleeding risk increased across quartiles of platelet count measured at VTE diagnosis (P for trend<0.02). In the age- and sex-adjusted model, subjects with platelet count in the highest quartile (≥300x109/L) had a 4.3-fold (95% CI 1.7–10.9) higher risk of major bleeding compared to those with platelet count in the lowest quartile (≤192x109/L), and exclusion of patients with cancer yielded similar results. When platelet count was measured on average 7 years before a VTE, the corresponding HR was 2.5 (95% CI 0.9–6.7). Our results suggest that increasing platelet count, assessed several years before and at VTE diagnosis, is associated with a higher risk of major bleeding, and could be a stable individual marker of major bleeding risk in VTE-patients.